Development of strut-and tie model for carbon fibre reinforced polymer strengthened deep beams - Panjehpour, Mohammad (2014)
Deep beams are commonly used in tall building, offshore structures and foundations. According to many codes and standards, strut-and-tie models (STM) are recommended as a rational approach to analyse discontinuity regions (D-regions) and consequently deep beams. Since the last decade, strengthening of reinforced concrete (RC) beams with carbon fibre reinforced polymer (CFRP) has become a topic of interest among researchers. However, STM is not able to predict shear strength of deep beams strengthened with CFRP sheet. There is a need for a rational model to predict the ultimate strength of CFRP strengthened deep beams is the significance of this research problem. This thesis elaborates on the STM recommended by ACI 318-11 and AASHTO LRFD using experimental results to point the way toward modifying a strut effectiveness factor in STM for CFRP strengthened RC deep beams. It addresses several ways to enhance our understanding of strut performance in the STM. The purpose of this research is to modify the STM for prediction of shear strength of RC deep beams strengthened with CFRP. Hence, the main objective of this research is to propose an empirical relationship to predict the strut effectiveness factor in STM for CFRP strengthened RC deep beams. Besides, the issue of energy absorption of CFRP strengthened RC deep beams is also discussed in this research. Twelve RC deep beams comprising six ordinary deep beams and six CFRP strengthened deep beams with shear span to the effective depth ratio of 0.75, 1.00, 1.25, 1.50, 1.75, and 2.00 were tested till failure in a fourpoint bending set up. The values of principal tensile strain perpendicular to strut centreline were measured using demountable mechanical strain gauge (DEMEC). Finally, a modified STM using an empirical relationship was proposed to predict the ultimate shear strength of CFRP strengthened RC deep beams. The modification of STM was made by proposing an empirical equation to predict the strut effectiveness factor in STM for CFRP strengthened RC deep beams. According to the experimental results the growth of energy absorption of CFRP strengthened RC deep beams varies from approximately 45% to 80% for shear span to effective depth ratio of 0.75 to 2.00 respectively. This research is confined to RC deep beams strengthened with one layer of CFRP sheet installed using two-side wet lay-up system.